Regulation for Hydraulic Fracturing in Unconventional Resources Exploration in Brazil (Research, Society and Development, 2022)
In Brazil, it is not yet possible to use hydraulic fracturing (fracking) to explore unconventional resources. Given (i) the attempt to bid unconventional areas in 2014; and (ii) the regulation of this exploration technique in the same period, discussions about the feasibility of this economic activity in the country emerged. National Agency of Petroleum, Natural Gas, and Biofuel promoted discussions with society on the subject. This article analyzed the regulatory processes of hydraulic fracturing in unconventional resources in Brazil to understand sensitive points to implement this practice in the country. By analyzing the processes and procedures adopted by the competent entities, especially the ANP, it was possible to understand how the regulatory process happened to glimpse improvements that may enable this activity in the future. The study result demonstrated that the first national implementation attempt preceded a specific norm to regulate the activity. However, the administrative processes that led to the 12th ANP Bidding Round and the preparation of ANP Resolution No. 21/2014 show that this was not even a sensitive point in employing these operations. The study concluded that, although there is room for regulatory improvement, the main obstacle to exploring this activity stems from the incipient geological data at the time of the 2014 bidding round.